2004
DOI: 10.1038/sj.ejcn.1601890
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dietary saturated fatty acids correlates with increased plasma lecithin cholesterol acyltransferase activity in humans

Abstract: Objective: Increased HDL-cholesterol (HDL-C) concentrations have been associated with lower coronary heart disease risk. On the other hand, dietary fats are known to influence the fatty acid profile of plasma lipids, including phospholipids that are substrates of lecithin cholesterol acyltransferase (LCAT), an important enzyme in HDL metabolism. The purpose of this study was to examine the association between the saturated fatty acid (SFA) intake and LCAT activity. Design: An interventional study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
8
1
1
Order By: Relevance
“…Our results on the LCAT endogenous activity contrast with those found by Bérard et al [14]. The authors compared a diet providing 11% TE as SFA with a diet that supplied a lower SFA content (8.4% TE), compensated by a higher carbohydrate content (+8%).…”
Section: Comparison Of Diet 2 Versus Dietcontrasting
confidence: 83%
See 1 more Smart Citation
“…Our results on the LCAT endogenous activity contrast with those found by Bérard et al [14]. The authors compared a diet providing 11% TE as SFA with a diet that supplied a lower SFA content (8.4% TE), compensated by a higher carbohydrate content (+8%).…”
Section: Comparison Of Diet 2 Versus Dietcontrasting
confidence: 83%
“…Moreover, Tholstrup et al [12] observed in humans the plasma HDLcholesterol level was 8% higher with a diet providing 16% total energy (TE) as MA compared with a diet providing 16% TE as palmitic acid (respectively, 1.10 ± 0.06 vs. 1.01 ± 0.05 mmol; P < 0.006). A recent study [14] has observed in humans an increase in HDL cholesterol concentrations by increasing SFA intake (from 8.4 to 11% TE), while plasma apo A-I concentration and LCAT activity both decreased (P < 0.02). On the other hand, in hypertriglyceridemic patients, a high-fat diet significantly increased HDL cholesterol and LCAT, while a subsequent low-fat diet decreased HDL cholesterol and LCAT [15].…”
Section: Introductionmentioning
confidence: 94%
“…For example, Jansen et al (75) observed that CETP concentrations were significantly elevated by 12 and 11 %, in individuals on a high SFA diet, compared with individuals on the National Cholesterol Education Program StepI diet and MUFA diet, respectively. Additionally, an elevation of SFA from 8·4 to 11 % decreased lecithin-cholesterol acyltransferase activity from 56 to 74 nM/ml per h, which may result in decreased reverse cholesterol transport and influence CVD risk (76) .…”
Section: Cholesterol Metabolism and Dietmentioning
confidence: 99%
“…2) There is an increase in the rate of cholesterol synthesis (Jones et al, 1994). 3) Modulation of RCT occurs (Berard et al, 2004;Jansen et al, 2000). RCT is affected in 2 ways.…”
Section: Comparison With Clinical Datamentioning
confidence: 99%